2014
DOI: 10.1186/s12881-014-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Hsa-mir-499 polymorphism (rs3746444) for cancer risk: evidence from 31 case-control studies

Abstract: BackgroundMicroRNAs (miRNAs) are a family of endogenous, small and non-coding RNAs that regulate gene expression negatively at the post-transcriptional level by suppressing translation or degrading target mRNAs, and are involved in diverse biological and pathological processes. Single nucleotide polymorphisms (SNPs) which are located in the miRNA-coding genes may participate in the process of development and diseases by altering the expression of mature miRNA. Recent studies investigating the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…Therefore, investigation of the relationship between genetic variants in noncoding genomic regions and gene function may help to improve our knowledge about the associations between genotypes and phenotypes. Previous studies in miRNA variation reported a high conservation of human miRNAs [Saunders et al., ; Quach et al., ]; and although several examples showing the association of miRNA genetic variants with disease have already been described [Jazdzewski et al., ; Hoffman et al., ; Jazdzewski et al., ; Xu et al., ; Xu et al., ; Lopez‐Valenzuela et al., ; Soldà et al., ; Chen et al., ; Fu et al., ; Hrdlickova et al., ; Wan et al., ; Xu et al., ; Zhou et al., ], there is still little information on the functional consequences that these genetic changes may have [Duan et al., ; Jazdzewski et al., ; Jazdzewski et al., ; Lopez‐Valenzuela et al., ; Ghanbari et al., ; Hill et al., ]. Here, we analyzed global genetic variation in miRNA regions among human populations and look for the functional differences between allele variants of three common miRNA SNVs that had repeatedly been associated with different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, investigation of the relationship between genetic variants in noncoding genomic regions and gene function may help to improve our knowledge about the associations between genotypes and phenotypes. Previous studies in miRNA variation reported a high conservation of human miRNAs [Saunders et al., ; Quach et al., ]; and although several examples showing the association of miRNA genetic variants with disease have already been described [Jazdzewski et al., ; Hoffman et al., ; Jazdzewski et al., ; Xu et al., ; Xu et al., ; Lopez‐Valenzuela et al., ; Soldà et al., ; Chen et al., ; Fu et al., ; Hrdlickova et al., ; Wan et al., ; Xu et al., ; Zhou et al., ], there is still little information on the functional consequences that these genetic changes may have [Duan et al., ; Jazdzewski et al., ; Jazdzewski et al., ; Lopez‐Valenzuela et al., ; Ghanbari et al., ; Hill et al., ]. Here, we analyzed global genetic variation in miRNA regions among human populations and look for the functional differences between allele variants of three common miRNA SNVs that had repeatedly been associated with different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…After an analysis of the global genetic variation in miRNAs, we thoroughly analyzed three miRNA SNVs associated with cancer [Chen et al., ; Fu et al., ; Wan et al., ; Xu et al., ; Zhou et al., ] located in the mature region of four miRNAs (two in the seed). miRNA overexpression experiments showed statistically significant differences in the expression between allele variants for all the analyzed SNVs, being the highest differences found in the cases of hsa‐miR‐146a‐3p and hsa‐miR‐196a‐3p (10.7 and 9.78, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-499a-5p, miR-499a-3p, miR499b are three family members exhibiting high sequence homology. Recent studies have shown that miRNA-499, which is highly conserved across species, inhibits cardiomyocyte progenitor cells proliferation and promotes cell differentiation (14). There is a positive feedback between the expression of miRNA-499 and some cardiac enriched transcription factors.…”
Section: Biology Of Mir-499 In Cardiomyocyte Developmentmentioning
confidence: 99%
“…For 51 SNPs identified by meta‐analysis, 38 SNPs had statistically significant association with EC or ESCC susceptibility . Meta‐analysis results showed that there were 27 SNPs associated with increased EC or ESCC risk, whereas 11 SNPs decreased the risk of EC or ESCC risk.…”
Section: Resultsmentioning
confidence: 94%